2018
DOI: 10.3390/insects9030098
|View full text |Cite
|
Sign up to set email alerts
|

Increased Adult Aedes aegypti and Culex quinquefasciatus (Diptera: Culicidae) Abundance in a Dengue Transmission Hotspot, Compared to a Coldspot, within Kaohsiung City, Taiwan

Abstract: The assumption that vector abundance differences might drive spatial and temporal heterogeneities in vector-borne disease transmission is common, though data supporting it is scarce. Here, we present data from two common mosquito species Aedes aegypti (Linnaeus) and Culex quinquefasciatus Say, biweekly sampled as adults, from March 2016 through December 2017, with BG-sentinel traps in two neighboring districts of Kaohsiung City (KC), Taiwan. One district has historically been a dengue transmission hotspot (San… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 97 publications
2
23
0
Order By: Relevance
“…In countries where dengue is endemic, mosquito activity was monitored for vector control interventions and to evaluate the effectiveness of control methods. Studies conducted in Taiwan indicated that mosquito abundance was a predictor of the dengue transmission risk [67] and that mosquito indices and climatic variables were early warning factors [68]. Herein, we found a positive association between container index and dengue transmission, suggesting that the mosquito population plays an important role in dengue fever transmission in central Vietnam.…”
Section: Discussionsupporting
confidence: 50%
“…In countries where dengue is endemic, mosquito activity was monitored for vector control interventions and to evaluate the effectiveness of control methods. Studies conducted in Taiwan indicated that mosquito abundance was a predictor of the dengue transmission risk [67] and that mosquito indices and climatic variables were early warning factors [68]. Herein, we found a positive association between container index and dengue transmission, suggesting that the mosquito population plays an important role in dengue fever transmission in central Vietnam.…”
Section: Discussionsupporting
confidence: 50%
“…The global public health burden of some vector-borne diseases has increased substantially in recent decades [1, 2]. The geographical distribution and abundance of vectors is strongly linked to transmission patterns of these diseases [3, 4]. There is growing concern that climate and land-use change, coupled with rapid globalization, may result in shifts in both the distributions of vector species and the diseases they transmit [5].…”
Section: Introductionmentioning
confidence: 99%
“…Kaohsiung was selected as the study area due to an abnormally increased incidence of dengue fever in 2014 and 2015 including 15,008 cases in Kaohsiung in 2014 and 19,710 cases in Kaohsiung in 2015. This is significantly higher than baseline, which encompassed approximately 300–2,000 cases annually in the preceding years, 2005–2013 [ 14 , 21 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between temperature and mosquito activity has been reported in many published papers [ 21 , 25 , 27 30 ], motivating us to establish the mosquito biting rate function. The biting rate (BR) is a function of temperature and is used instead of temperature to explore the relationship with dengue case number.…”
Section: Methodsmentioning
confidence: 99%